Analysis of interfacial stresses of composite bridge box steel-concrete beam - Benferhat, R.; Daouadji, T. Hassaine; Abbes, B.; Bensatallah, T.; Rabahi, A.; Abbes, F. (Coupled Systems Mechanics, 2025)
This study investigates the flexural reinforcement of composite box girder bridge decks through combined analytical and numerical approaches using ABAQUS software. The research focuses on deflection, interface stresses, and interfacial slip, while also examining the role of reinforcement type, adhesive properties, and the presence of deck openings. A comprehensive parametric study highlights that material selection, reinforcement configuration, and adhesive characteristics significantly affect structural performance. Moreover, deck openings are shown to increase interfacial stresses and slip due to stress concentration and redistribution.